Pondoks, Madrasahs, and the Production of Ulama in Malaysia - William R. Roff (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
This essay traces the development of pondoks, or peoples' Islamic schools (sekolah ngama rakyat), in nineteenth and twentieth century Malay peasant society, their evolution into institutions styled madrasahs, and the role both played in the production of 'ulama'. Their equivalents in Indonesia, generally known as pesantren, have been the subject of substantial research and several notable published studies. Though this has been much less true for Malaysia, the scattered material that does exist perhaps warrants the following attempt to piece it together.DOI: 10.15408/sdi.v11i1.651